Terra-i+ website: Satellite based solution for Agroforestry Supply Chain Sustainability (https://www.terra-iplus.org/) - Vantalon, Thibaud; Talsma, Tiffany; Reymondin, Louis; Nguyen, Phuong Minh; Luong, Phuong Thi; Bunn, Christian; Nguyen Thi, Thuy Thu; Phan, Trong Van; Castro Llanos, Fabio Alexander; Paz Garcia, Paula Andrea; Pérez Escobar, Jorge Andres; Tello Dagua, Jhon Jairo (2023)
Terra-i+ is a website that uses remote sensing technology to help supplier-sourced agribusinesses monitor and report on geospatial data for purpose of EU Deforestation Regulation compliance, certification management, and carbon project management.